Declarations of Unconstitutionality in the Common Law Tradition: A Comparative and Theoretical Analysis - NOONAN, ROBERT (Trinity College Dublin. School of Law. Discipline of Law, 2019)
This thesis is a comparative and theoretical study of declarations of unconstitutionality. It combines a comparative analysis of the laws of Ireland, Canada, the United States, India and South Africa with a jurisprudential analysis of philosophical issues that inform unconstitutionality as a general legal phenomenon. Constitutional orders in which judges have a full power of judicial review of legislation must invariably confront the difficulty of unconstitutional law. Through comparative doctrinal analysis, I argue that there are three questions a theory of unconstitutionality must answer: the derivation question, the effects question, and the temporal question. The derivation question accounts for the source of unconstitutionality and answers, from a more technocratic point of view, how unconstitutionality is brought about in the first place. The effects question addresses how unconstitutionality modifies the properties of legal norms. Finally, the temporal question attends to when unconstitutionality begins, and for how long it is effective. Using these questions, I present a scheme for rationalising the practice of the studied jurisdictions, and I propose a new model of unconstitutionality. The thesis thus both deepens knowledge of the law as it stands and makes normative proposals for improving theory and practice in this area. The comparative analysis highlights the common treatment of unconstitutional law as being invalid and void ab initio. This view of unconstitutional law is widespread, and invariably generates difficulty. The thesis criticises this view, though the framework of unconstitutionality generated by the three questions above, and proposes an alternative theory as a possible replacement. The thesis proposes that legal validity should not be treated as entailing fixed answers to the applicability of unconstitutional legal norms. The thesis demonstrates, using theoretical argument and data from the comparative study, how legal validity and applicability are distinct properties of legal norms, and how treating these properties separately can deepen understanding of unconstitutionality and produce less severe contagion effects where unconstitutionality is apprehended. It can also assist in developing a more sophisticated understanding of important public law remedies, such as the suspended declaration of invalidity. This inspires both a more edifying theory of unconstitutionality and a more equitable practice. The preferred model of unconstitutionality in this thesis is developed on a ?choice of law? analogy that coheres with a detailed theory of legal systems also endorsed by this thesis. This model is both theoretically and practically preferable to competitor models and, if adopted by courts, it would produce new legal doctrines that deal more sensibly with the moral dimensions of retrospectively imposing changes to legal rules. This would provide much-needed clarity in this important area of public law.
APPROVED
Keywords: constitutional law; law; unconstitutionality; jurisprudence; legal validity; public law; judicial review